Packaging adhesive and preparation method thereof
By blending and modification of trimethoxysilane-terminated polyether and polyurethane-modified epoxy resin, a new packaging adhesive was prepared, which solved the problem of the use of existing adhesives at high and low temperatures. It is environmentally friendly and suitable for PACK frame sealing and cell bonding of power batteries.
Patent Information
- Application Number
- CN202411808292.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing power battery pack structural glue, especially PACK packaging glue, has problems such as poor moisture and heat resistance, poor high temperature resistance, and poor flexibility at low temperatures. At the same time, free NCO is present, which is not environmentally friendly.
The blending and modification of trimethoxysilane-terminated polyether and polyurethane-modified epoxy resin is used to form an interpenetrating network structure. Combining the advantages of epoxy resin and silane-modified polyether, a new packaging adhesive is prepared.
This packaging adhesive has excellent temperature resistance, low temperature modulus, good aging performance, strong airtightness, good adaptability to substrates, and is suitable for PACK frame sealing and cell bonding of power batteries, providing long-term comprehensive protection, and is environmentally friendly.
Smart Images

Figure BDA0005179872880000021 
Figure BDA0005179872880000041 
Figure BDA0005179872880000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a packaging adhesive and a preparation method thereof. Background Art
[0002] In recent years, my country's new energy vehicle industry has developed rapidly, and a large number of models with high product quality, high technical level and good user experience have emerged, which are widely welcomed by domestic and foreign consumers. In 2023, my country's production and sales of new energy vehicles will reach 9.587 million and 9.495 million respectively, an increase of 35.8% and 37.9% respectively over the previous year. The production and sales volume has ranked first in the world for 9 consecutive years, and the sales volume accounts for 31.6% of the total automobile sales. New energy electric vehicles are a mainstream development trend to solve energy, environment, urban transportation and other problems, and are also a major direction for the development of the future automobile manufacturing industry.
[0003] Power storage batteries are the core part of new energy vehicles, which determine the safety, life and performance of new energy vehicles. They are also one of the most expensive parts of new energy vehicles, accounting for more than 50% of the whole vehicle. As an important material for battery assembly, adhesives play a vital role in automotive power batteries, profoundly affecting the output efficiency, charging speed, heat dissipation and safety of power batteries. At present, the wave of electrification is sweeping the world, and the demand for power batteries is growing explosively, and the scale of the adhesive market is also expanding simultaneously.
[0004] Power battery technology is undergoing rapid iteration and upgrading, with new products emerging continuously. The development of new adhesive materials that are adapted to the technology is essential for improving the energy density, safety, cycle life and lightweight of power batteries. Adhesives have four major functions in power batteries: first, providing protection for power batteries; second, achieving safe and reliable lightweight design; third, thermal management; and fourth, helping batteries cope with more complex usage environments.
[0005] In the field of new energy vehicles, adhesive products are mainly used in power battery management systems (BMS) and the same type of new energy storage battery modules for protection, thermal conductivity, bonding and fixation, and other diversified scenarios; products are used in the thermal management system of battery PACKs to play the role of thermal conductivity, potting, and protection. Adhesives can enter the power battery PACK industry. In order to solve the safety and reliability of power batteries, it is necessary to comprehensively consider anti-collision and shockproof, flame retardant, thermal conductivity, waterproof and other aspects to create the most reliable solution for customers.
[0006] At present, the power battery pack structural adhesive on the market, especially PACK packaging adhesive, is mainly polyurethane structural adhesive. Polyurethane structural adhesive has good elasticity and tensile properties, excellent seismic resistance, and is wear-resistant, cold-resistant, and oil-resistant. However, polyurethane structural adhesive has poor resistance to moisture and heat aging, poor high temperature resistance, and poor flexibility at low temperatures, which seriously affects the use of batteries under high and low temperature conditions. At the same time, polyurethane structural adhesive contains free NCO, which is not friendly to the environment. Therefore, it is imperative to develop a PACK packaging adhesive for power batteries with excellent bonding performance, low low-temperature modulus, and environmental friendliness in the field of new energy battery adhesives. Summary of the invention
[0007] In view of the deficiencies of the above-mentioned prior art, the present invention provides a power battery box PACK packaging adhesive and a preparation method thereof. The specific technical scheme is as follows:
[0008] The first object of the present invention is to provide a packaging adhesive, comprising component A and component B:
[0009] Component A, by weight, includes the following components:
[0010] 50-85 parts of trimethoxysilane-terminated polyether, 5-10 parts of epoxy curing agent, 1-5 parts of coupling agent, 1-3 parts of water scavenger, and 15-40 parts of filler;
[0011] The structural formula of the trimethoxysilane-terminated polyether is shown in formula (I):
[0012]
[0013] Wherein, n = 20-40;
[0014] Component B, by weight, includes the following components:
[0015] Polyurethane modified epoxy resin 45-85 parts, plasticizer 10-30 parts, catalyst 0.5-3 parts, water 1-3 parts, filler 15-45 parts;
[0016] The mass ratio of the component A to the component B is 1:(0.8-1.2).
[0017] The trimethoxy-modified silane-terminated polyether in the component A of the encapsulation adhesive of the present invention has a main chain structure composed of silane-terminated polyether units and polyurethane structural units, achieving good flexibility. Compared with traditional rubber-modified or ethylene oxide-modified flexible epoxy resins, it has higher elongation, lower elastic modulus, higher impact resistance and heat resistance, and has good compatibility with other epoxy resins; the structure of four (-CH2-)s connected in two ether bonds, when the number of (-CH2-)s in the molecular chain is an even number, the material has better crystallinity, resulting in large intermolecular attraction and close molecular arrangement.
[0018] The invention adopts the method of blending and modifying the trimethoxy-modified silane-terminated polyether of formula (I) and the epoxy resin, so that the epoxy resin and the trimethoxy-modified silane-terminated polyether dual system form an interpenetrating network structure, and form an island structure after curing, thereby retaining the bonding strength of the epoxy resin to metal and plastic substrates, and increasing the toughness and tensile properties of the adhesive material, effectively combining the advantages of the epoxy resin and the silane-modified polyether, and overcoming the limitations of traditional adhesives.
[0019] Furthermore, the preparation method of the trimethoxysilane-terminated polyether is:
[0020] At room temperature, polytetrahydrofuran diol (PTMG) is heated to 30-50°C, stirred at a constant temperature until it becomes a uniform, lump-free liquid, then the temperature is raised to 110-120°C, vacuumed and stirred for 1-3 hours, then cooled to 50-70°C, a silane coupling agent containing NCO is added, then the temperature is raised to 75-90°C, vacuumed and stirred for 1-3 hours, then the reaction is stopped and the material is discharged.
[0021] The trimethoxysilane-terminated polyether is formed by polymerizing tetrahydrofuran diol and a silane coupling agent containing NCO. As a polyether, polytetrahydrofuran diol has very good flexibility. The polyether prepared by using polytetrahydrofuran diol as a soft segment has the advantages of good toughness, solvent resistance, hydrolysis resistance and the like. The glass transition temperature of polytetrahydrofuran diol can be as low as -70 DEG C. The silane-modified polyether obtained by polymerizing polytetrahydrofuran diol and a silane coupling agent containing NCO has very good low-temperature resistance.
[0022] Furthermore, the relative molecular mass of the polytetrahydrofuran diol is 2000 (PTMG2000); and the silane coupling agent is 3-isocyanate propyltrimethoxysilane.
[0023] The reaction equation is as follows:
[0024]
[0025] Furthermore, the epoxy curing agent is one or more of polyetheramine D2000, polyetheramine D400, and polyetheramine D230.
[0026] The epoxy curing agent of the present invention uses a polyetheramine curing agent, the main chain of which is a polyether structure, and it has good flexibility itself. It is a flexible epoxy curing agent and has good compatibility with epoxy resin. The cured body has excellent toughness and fatigue resistance, good water resistance and heat resistance, and can be used for a long time in a humid and high temperature environment. At the same time, it is not easy to age and break.
[0027] Furthermore, the coupling agent is one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and aminopropyltriethoxysilane.
[0028] Furthermore, the dehydrating agent is vinyltrimethoxysilane.
[0029] Furthermore, the epoxy equivalent of the polyurethane modified epoxy resin is between 600-900 g / eq, and the structural formula is shown in formula (II):
[0030]
[0031] Wherein, R is CH3; m=2-5, n=1-4.
[0032] Furthermore, the plasticizer is polypropylene glycol 2000, which can enhance the flexibility and ductility of the toughening agent solidified body, and its presence can also improve the adhesion and durability of the adhesive to plastics and metals.
[0033] Furthermore, the catalyst is one or more of dibutyltin dilaurate, chelated tin, and bismuth titanate; and the water is homemade deionized water.
[0034] Furthermore, the filler is nano calcium carbonate treated with a silane coupling agent, and the specific method is as follows:
[0035] The nano calcium carbonate powder is heated to 70-120°C, and then atomized silane coupling agent is sprayed on the nano calcium carbonate powder, and stirred while spraying. After the spraying is completed, the powder is placed in an oven for drying for standby use; the mass of the silane coupling agent is 0.5-3% of the nano calcium carbonate powder. The silane coupling agent is KH550, KH560 and similar silane coupling agents.
[0036] The second object of the present invention is to provide a method for preparing the above-mentioned packaging adhesive, comprising the following steps:
[0037] (1) Preparation of component A:
[0038] A1: Add trimethoxysilane-terminated polyether, epoxy curing agent, filler and coupling agent into a reaction vessel and stir under vacuum at 20-30°C for 1-3h;
[0039] A2: Continue to take samples at 20-30℃ to test the water content. When the water content is ≤800ppm, add dehydrating agent and stir in vacuum for 20-40min. Then cool to room temperature and stir in vacuum for 1-2h before discharging.
[0040] (2) Preparation of component B:
[0041] B1: Add polyurethane modified epoxy resin, plasticizer and filler into the reaction vessel, vacuum and stir at 20-30℃ for 0.5-2h;
[0042] B2: Add catalyst and water, stir under vacuum at 20-30℃ for 20-40min, and discharge.
[0043] When using the double tube packaging, simply insert the tube into the application gun and discharge a small amount of adhesive, ensuring even and free flow on both sides; if automatic mixing of components A and B is required, connect the mixing nozzle to the automatic mixer and start dispensing components A and B; when mixing manually, discharge the required amount of components A and B and mix thoroughly for 15 seconds.
[0044] When using bulk containers, thoroughly mix Part A and Part B in proportion by weight for approximately 15 seconds.
[0045] When used to bond substrates, the following steps are included:
[0046] The encapsulation adhesive is evenly applied on the surface of a substrate or two substrates to be connected; the coating should be completed within 40-60 minutes of the applicable time, and the two substrates are in contact with each other; movement is prevented during the curing process, and contact pressure is applied when necessary, and the curing is completed at room temperature.
[0047] For high-strength structural parts, remove substrate surface contamination such as paint, oxide film, oil, dust, release agent and all other surface contamination.
[0048] The beneficial effects of the present invention are:
[0049] The packaging adhesive provided by the present invention has excellent temperature resistance, good colloid flexibility, low modulus at low temperature, and excellent aging performance. After the A and B components are mixed and cured, a cured body with excellent sealing performance, good air tightness, and good adaptability to the substrate is formed. The cured body can be used for PACK frame sealing in power batteries, bonding between battery cells, between battery cells and heat dissipation components, and between battery cells and modules. The packaging adhesive is a packaging material that provides long-term and comprehensive protection for power batteries. In addition, the A and B components do not contain volatiles and have low odor, which is beneficial to the use environment and operators. DETAILED DESCRIPTION
[0050] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0051] Homemade trimethoxysilane-terminated polyether:
[0052] By weight, at room temperature, PTMG2000 is added to a three-necked flask, and then the temperature is raised to 40°C, and the temperature is kept constant at 40°C for 10 minutes. The state of the reactants is observed to be a uniform, non-agglomerated liquid, and then the temperature of the heating jacket is adjusted to raise the material temperature to 115°C and evacuate to -0.1MPa, and after stirring for 2 hours, the temperature is lowered to 60°C, and NCO-containing silane coupling agent 3-isocyanate propyltrimethoxysilane is added, and then the temperature is raised to 80°C, and the reaction is stopped after vacuum stirring for 2 hours. The molar ratio of PTMG2000 to the silane coupling agent 3-isocyanate propyltrimethoxysilane is 1:2.
[0053] Pretreatment of filler:
[0054] Silane coupling agent KH570 accounting for 1.5% of the total mass of nano calcium carbonate powder is placed in the liquid storage tank of the spray equipment, and then the nano calcium carbonate powder with a particle size D50 ranging from 10-15μm accounting for 97-99.5% of the total amount is heated to 80°C, the spray equipment switch is turned on, and the atomized silane coupling agent KH570 is sprayed while stirring. After spraying, it is placed in a 110°C oven for drying for 16 hours for use.
[0055] Embodiment 1:
[0056] A packaging adhesive comprises the following components in parts by weight:
[0057] Component A: 80 parts of trimethoxysilane-terminated polyether (self-made), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.5 parts of water scavenger vinyltrimethoxysilane, 22 parts of filler (pre-treated);
[0058] Component B: 65 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 27 parts of plasticizer polypropylene glycol 2000, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 23 parts of filler (pre-treated);
[0059] The preparation method of the packaging adhesive comprises the following steps:
[0060] (1) Preparation of component A
[0061] A1: Add trimethoxysilane-terminated polyether, epoxy curing agent, filler and coupling agent into a reaction vessel, stir for 2 h at 25°C, vacuum degree -0.1 MPa and stirring speed of 600 rpm;
[0062] A2: Continue to maintain the temperature at 25°C, take samples to test the moisture content, and when the moisture content is ≤800ppm, add a desiccant, evacuate to -0.1MPa, stir at 600rpm, and stir for 30min; then cool to room temperature, evacuate to -0.1MPa, stir at 600rpm, stir for 1.5h, and discharge and pipe.
[0063] (2) Preparation of component B:
[0064] B1: Add polyurethane modified epoxy resin, filler and plasticizer into the reaction vessel, evacuate to -0.1MPa at 25℃, stir at 600rpm, and stir for 1h;
[0065] B2: Add catalyst and water, continue to evacuate, vacuum -0.1MPa, 25℃, stirring speed 600rpm, stir for 30min, discharge and pipe.
[0066] Post-processing: With the help of a centrifuge, centrifuge the double-tube packaged adhesive at 800 rpm for 5 minutes at room temperature to remove bubbles, and store the finished product at room temperature.
[0067] Embodiment 2:
[0068] A packaging adhesive comprises the following components in parts by weight:
[0069] Component A: 78 parts of trimethoxysilane-terminated polyether (self-made), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.5 parts of water scavenger vinyltrimethoxysilane, 24 parts of filler (pre-treated);
[0070] Component B: 64 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 28 parts of plasticizer polypropylene glycol 2000, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 23 parts of filler (pre-treated);
[0071] The preparation of the packaging adhesive is the same as that in Example 1 and will not be described in detail here.
[0072] Embodiment 3:
[0073] A packaging adhesive comprises the following components in parts by weight:
[0074] Component A: 76 parts of trimethoxysilane-terminated polyether (self-made), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.2 parts of water scavenger vinyltrimethoxysilane, 26 parts of filler (pre-treated);
[0075] Component B: 63 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 29 parts of plasticizer polypropylene glycol 2000, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 23 parts of filler (pre-treated);
[0076] The preparation of the packaging adhesive is the same as that in Example 1 and will not be described in detail here.
[0077] Embodiment 4:
[0078] A packaging adhesive comprises the following components in parts by weight:
[0079] Component A: 74 parts of trimethoxysilane-terminated polyether (self-made), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.5 parts of water scavenger vinyltrimethoxysilane, 28 parts of filler (pre-treated);
[0080] Component B: 62 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 30 parts of plasticizer polypropylene glycol 2000, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 23 parts of filler (pre-treated);
[0081] The preparation of the packaging adhesive is the same as that in Example 1 and will not be described in detail here.
[0082] Comparative Example 1:
[0083] A packaging adhesive comprises the following components in parts by weight:
[0084] Component A: 90 parts of trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500), 8 parts of epoxy curing agent polyetheramine D230, 1.5 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 0 parts of water scavenger vinyltrimethoxysilane, 23 parts of filler (pretreatment);
[0085] Component B: 92 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 2000 parts of plasticizer polypropylene glycol, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 23 parts of filler (pre-treated);
[0086] The preparation of the encapsulation adhesive is different from that of Example 1 in that "trimethoxysilane-terminated polyether (homemade)" is replaced with "trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500)", and the rest is the same and will not be repeated here.
[0087] Comparative Example 2:
[0088] A packaging adhesive comprises the following components in parts by weight:
[0089] Component A: 88 parts of trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.5 parts of water scavenger vinyltrimethoxysilane, 14 parts of filler (pretreatment);
[0090] Component B: 65 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 2000 parts of plasticizer polypropylene glycol, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 25 parts of filler (pre-treated);
[0091] The preparation of the encapsulation adhesive is different from that of Example 1 in that "trimethoxysilane-terminated polyether (homemade)" is replaced with "trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500)", and the rest is the same and will not be repeated here.
[0092] Comparative Example 3
[0093] A packaging adhesive comprises the following components in parts by weight:
[0094] Component A: 80 parts of trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.5 parts of water scavenger vinyltrimethoxysilane, 22 parts of filler (pre-treated);
[0095] Component B: 65 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 27 parts of plasticizer polypropylene glycol 2000, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 23 parts of filler (pre-treated);
[0096] The preparation of the encapsulation adhesive is different from that of Example 1 in that "trimethoxysilane-terminated polyether (homemade)" is replaced with "trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500)", and the rest is the same and will not be repeated here.
[0097] Comparative Example 4
[0098] A packaging adhesive comprises the following components in parts by weight:
[0099] Component A: 84 parts of trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500), 8 parts of epoxy curing agent polyetheramine D230, 1.2 parts of coupling agent γ-methacryloxypropyltrimethoxysilane, 1.5 parts of water scavenger vinyltrimethoxysilane, 16 parts of filler (pre-treatment);
[0100] Component B: 65 parts of polyurethane modified epoxy resin (ENC-3801 from Hunan Saierwei Materials Co., Ltd.), 28 parts of plasticizer polypropylene glycol 2000, 1.2 parts of catalyst chelated tin, 1.5 parts of deionized water, and 25 parts of filler (pre-treated);
[0101] The preparation of the encapsulation adhesive is different from that of Example 1 in that "trimethoxysilane-terminated polyether (homemade)" is replaced with "trimethoxy-modified silane-terminated polyether (Shandong Lingxiao New Materials Co., Ltd., 3500)", and the rest is the same and will not be repeated here.
[0102] Detection:
[0103] According to the method of using the encapsulation adhesive, the mixing nozzle is connected to the automatic mixer, and the glue is discharged and applied with the help of the mixing glue gun for testing:
[0104] Working time: The time from the preparation of multi-component adhesive to the time when the adhesive can maintain its performance. Under standard conditions, 2g of mixed adhesive is applied to the egg tart cup and a toothpick is used to slide until the scratch is irreversible.
[0105] Hardness: The ability of a material to partially resist a hard object from pressing into its surface is called hardness. Prepare fully cured test pieces for testing: the thickness should be at least 6mm, and 3 layers of 2mm test pieces or 2 layers of 3mm test pieces can be stacked; the area should be at least 100mm*100mm, and the test point should be at least 15mm away from the edge; the surface near the test point should be flat and parallel up and down. According to the operating instructions of the hardness tester, the test sample should be cured at room temperature for 7 days, and the surface hardness should be tested at room temperature: the maximum pressing speed should be 3.2mm / s, and the pressing should be maintained for 3s. At least 5 sets of data should be read from 5 different places and averaged.
[0106] Modulus: (ASTM E1640-13 Standard Test Method for Assignment of the Glass Transition Temperature By Dynamic Mechanical Analysis), sample size thickness × width × length is between 1 × 5 × 20 mm and 1 × 10 × 50 mm; temperature range is -40 ° C ~ 85 ° C, heating rate is 1 ° C / min, using a tensile fixture, test frequencies include 33 Hz and 1 Hz, amplitude is 0.1 clamp length.
[0107] Pull-out strength: also called pull-out force test, is a method to evaluate the strength or endurance of materials or products during stretching or pulling. (GB / T 6329 Determination of tensile strength of adhesive butt joints) The sample joint is formed by the butt joint of two square or round rod-shaped adherends, and the bonding surface is perpendicular to the longitudinal axis of the sample. The tensile force is transmitted to the bonding surface through the longitudinal axis of the sample until the sample is destroyed. The load when the sample is destroyed is the test result.
[0108] The material of the test bar is 6061 aluminum: unless otherwise specified, the size of the test bar shall comply with the following provisions: the diameter of the round test bar is 10mm, 15mm, 25mm or 50mm, and the side length of the square test bar is 10mm, 15mm, 25mm or 50mm. The error range of the above dimensions is ±0.1mm; the length of the test bar with a diameter or side length of 10mm or 15mm is 3 times the diameter or side length, and the length of the test bar with a diameter or side length of 25mm or 50mm is 50mm. The bonding surface of the test bar should be flat and perpendicular to the longitudinal axis of the test bar. The other end of the test bar opposite to the bonding surface should have a pin hole that can be connected to the clamp of the tensile machine. Sufficient adhesive should be used for the bonded joint, and there should be a little excess glue around the joint to avoid insufficient glue joints. Excess glue usually does not need to be removed. If it must be removed, it must be done before hardening. After hardening, the specimen should be tested under no pressure. If there is no special provision, the number of specimens should not be less than 5. The test conditions are recommended to be carried out at 23±2℃ and 50±5 parts relative humidity. Al-PET-Al sandwich drawing specimen, both sides are 0.2mm thick, copper wire or rubber strip thickness limit; tensile rate is 5mm / min.
[0109] Shear strength: Apply longitudinal tensile shear force on the overlapped surface of the sample to determine the maximum load that the sample can withstand. Under standard conditions, grinded carbon steel is evenly glued and overlapped and fixed. After 24 hours of timing, the test machine is started and loaded at a stable speed within 10mm / min. The maximum load of the sample shear failure is recorded, and the length and width of the overlapped surface of the sample are measured with a measuring tool to calculate the tensile shear strength.
[0110] Tensile strength and elongation at break: Tensile strength is the maximum stress that a material can withstand during the stretching process. Elongation at break is the ratio of the maximum deformation of a material before it breaks during the stretching process to its original length. Prepare a 2mm thick adhesive curing sample to ensure that the surface is flat, smooth and pollution-free. After the sample is fully cured, let it stand in a laboratory environment for 3 hours, and then use an I-type dumbbell cutter to cut out standard specimens. The number of specimens should be at least 3.
[0111] Thermal shock: To test the ability to withstand thermal shock, use a thermal shock tester to continuously expose the device to -40°C for 30 minutes, then quickly switch to 85°C for 30 minutes. Repeat this cycle 100 times.
[0112] Damp heat aging: According to GB / T 2423.3 Environmental Test Part 2: Test Method Test Cab: Constant Damp Heat Test, place the sample in a constant temperature and humidity chamber with the temperature set to 85±3℃ and the humidity set to 82-88 parts RH for 1000 hours, then take it out and place it at room temperature for another 2 hours. Perform performance test according to standard test methods
[0113] The test results are shown in Table 1:
[0114] Table 1 Test results
[0115]
[0116] It can be seen from the data in Table 1 that the encapsulation adhesives of Examples 1 to 4 have bulk strength and shear strength after curing that are ≥10MPa, elongation at break>180%, modulus>300MPa, and the modulus is still very low at -40°C. It is an environmentally friendly adhesive with good low-temperature flexibility and does not contain NCO. The shear strength attenuation rate after hot and cold shock and wet heat aging is low, and the strength retention rate is>90%. The shear strength, tensile strength, bulk strength, elongation at break and modulus of Comparative Examples 1-4 are all lower than those of the Examples, and the shear strength attenuation rate after aging is higher than that of the Examples.
[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A packaging adhesive, characterized in that: Including component A and component B: Component A, by weight, includes the following components: 50-85 parts of trimethoxysilane-terminated polyether, 5-10 parts of epoxy curing agent, 1-5 parts of coupling agent, 1-3 parts of water scavenger, and 15-40 parts of filler; The structural formula of the trimethoxysilane-terminated polyether is shown in formula (I): Wherein, n = 20-40; Component B, by weight, includes the following components: Polyurethane modified epoxy resin 45-85 parts, plasticizer 10-30 parts, catalyst 0.5-3 parts, water 1-3 parts, filler 15-45 parts; The mass ratio of the component A to the component B is 1:(0.8-1.2).
2. The packaging adhesive according to claim 1, characterized in that The preparation method of the trimethoxysilane-terminated polyether is: At room temperature, the polytetrahydrofuran diol is heated to 30-50° C., stirred at a constant temperature until it becomes a uniform, lump-free liquid, then the temperature is raised to 110-120° C., vacuumed and stirred for 1-3 hours, then cooled to 50-70° C., a silane coupling agent containing NCO is added, then the temperature is raised to 75-90° C., vacuumed and stirred for 1-3 hours, then the reaction is stopped and the material is discharged.
3. The packaging adhesive according to claim 2, characterized in that The relative molecular mass of the polytetrahydrofuran diol is 2000; and the silane coupling agent is 3-isocyanate propyltrimethoxysilane.
4. The packaging adhesive according to claim 1, characterized in that The epoxy curing agent is one or more of polyetheramine D2000, polyetheramine D400 and polyetheramine D230.
5. The packaging adhesive according to claim 1, characterized in that The coupling agent is one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and aminopropyltriethoxysilane; and the dehydrating agent is vinyltrimethoxysilane.
6. The packaging adhesive according to claim 1, characterized in that The polyurethane modified epoxy resin has an epoxy equivalent of 600-900 g / eq, and a structural formula as shown in formula (II): Wherein, R is CH3; m=2-5, n=1-4.
7. The packaging adhesive according to claim 1, characterized in that: The plasticizer is polypropylene glycol 2000.
8. The packaging adhesive according to claim 1, characterized in that The catalyst is one or more of dibutyltin dilaurate, chelated tin, and bismuth titanate; and the water is homemade deionized water.
9. The packaging adhesive according to claim 1, characterized in that: The filler is nano calcium carbonate treated with a silane coupling agent, and the specific method is as follows: The nano calcium carbonate powder is heated to 70-120° C., and then atomized silane coupling agent is sprayed on the nano calcium carbonate powder while stirring. After the spraying is completed, the powder is placed in an oven for drying for standby use; the mass of the silane coupling agent is 0.5-3% of the nano calcium carbonate powder.
10. A method for preparing the packaging adhesive according to claims 1-9, characterized in that: The steps include: (1) Preparation of component A: A1: Add trimethoxysilane-terminated polyether, epoxy curing agent, filler and coupling agent into a reaction vessel and stir under vacuum at 20-30°C for 1-3h; A2: Continue to maintain the temperature at 20-30℃, take samples to test the water content, and when the water content is ≤800ppm, add dehydrating agent and stir under vacuum for 20-40min; then cool to room temperature and stir under vacuum for 1-2h before discharging; (2) Preparation of component B: B1: Add polyurethane modified epoxy resin, plasticizer and filler into the reaction vessel, vacuum and stir for 0.5-2h at 20-30℃; B2: Add catalyst and water, stir under vacuum at 20-30°C for 20-40 minutes, and discharge.
Citation Information
Patent Citations
Waterproof sealing gum for electronic product
CN108676537A
Preparation method of two-component room temperature rapid curing adhesive with anti-seismic heat-conducting structure
CN109337630A
Power battery structure bonding and box cover sealing double-component adhesive and preparation method thereof
CN109355053A
High-temperature-resistant silane modified adhesive as well as preparation method and application thereof
CN111117546A
Bi-component structural adhesive for bonding power battery and preparation method of bi-component structural adhesive
CN115558452A
Cited By
Flame-retardant heat-conducting multi-element hybrid structural adhesive for new energy lithium battery and preparation method thereof
CN120041131A